2020
DOI: 10.1088/1402-4896/ab51ee
|View full text |Cite
|
Sign up to set email alerts
|

Water and hydrogen transport modelling through the membrane-electrode assembly of a PEM fuel cell

Abstract: Membrane electrode assembly (MEA) formed by a proton exchange membrane (PEM), two catalyst layers and two gas diffusion layers represent the heart of the PEM fuel cell system, being the place where the electrochemical reactions are developed in order to generate electrical power. Due to a complex water production and transportation process through the porous media of MEA, the water management represents one of the most critical issues for the low temperature PEM fuel cell systems, working at 30 °C-80 °C. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Rahman et al developed a 1D non-isothermal model to predict the resistance to dry oxygen and limiting current. Ionescu developed a 1D model to study the net water flux and hydrogen crossover across the Nafion membrane in the PEM fuel cell. The study results showed that the cell performance improves as the cell pressure and temperature increase.…”
Section: Numerical Modeling Of Pem Fuel Cellsmentioning
confidence: 99%
“…Rahman et al developed a 1D non-isothermal model to predict the resistance to dry oxygen and limiting current. Ionescu developed a 1D model to study the net water flux and hydrogen crossover across the Nafion membrane in the PEM fuel cell. The study results showed that the cell performance improves as the cell pressure and temperature increase.…”
Section: Numerical Modeling Of Pem Fuel Cellsmentioning
confidence: 99%
“…Additionally, its hardware includes bipolar plates containing flow fields inside to channel the flow and gaskets enabling a gas-tight seal of the MEA. Its catalytic efficiency depends on the formation of triple-phase boundaries (TPBs) between the electrolyte, the electrocatalyst, and the gaseous product with reduced resistance of mass transfer and charge transfer [26,27]. Therein, besides facilitating mass transport of the products, GDL is also expected to conduct the electrons from the CL to bipolar plates and provide mechanical support for the membrane [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…One of the important parameters to be managed for PFSA membranes is the electro-osmotic drag (EOD) coefficient. It is defined as the ratio between the number of water molecules and protons transferred across the membrane in the absence of gradients in concentration and pressure and at vanishing electric field , Here, ξ D is the EOD coefficient of water in the membrane, is the flux of water, and is the flux of protons across the membrane in the presence of the electric field. While the definition of the EOD coefficient is straightforward, many attempts have been made to rationalize and quantify this parameter using experiments and simulations. ,,, As it will be discussed in this paper, the results of different experiments and simulation methods show a large scattering.…”
Section: Introductionmentioning
confidence: 99%